Penerapan Metode Weighted Product dan Rank Order Centroid dalam Penilaian Kinerja Staff Adminstrasi - Abdullah, Muksin Hi (Journal of Data Science and Information Systems, 2024)
The performance of administrative staff is very important in maintaining the smooth operation of an organization. The quality of the performance of administrative staff has a direct impact on the efficiency and effectiveness of various departments in the organization. The ability to manage high workloads, maintain information confidentiality, and interact with various parties, including internal and external employees, are important aspects in assessing the quality of administrative staff performance. This study aims to assess the performance of administrative staff by applying the Weighted Product and Centroid Order Rank methods so that it can be a foundation for leaders in assessing the performance of administrative staff. The results of the alternative ranking for rank 1 with a value of 0.1755 were obtained by an alternative on behalf of Haris, rank 2 with a value of 0.1711 was obtained by an alternative on behalf of Yuni, rank 3 with a value of 0.1710 was obtained by an alternative on behalf of Andini.